The Tsimane Health and Life History Project: Integrating anthropology and biomedicine. Issue 2 (April 2017) - Gurven, Michael; Stieglitz, Jonathan; Trumble, Benjamin; Blackwell, Aaron D.; Beheim, Bret; Davis, Helen; Hooper, Paul; Kaplan, Hillard
Abstract: The Tsimane Health and Life History Project, an integrated bio‐behavioral study of the human life course, is designed to test competing hypotheses of human life‐history evolution. One aim is to understand the bidirectional connections between life history and social behavior in a high‐fertility, kin‐based context lacking amenities of modern urban life (e.g. sanitation, banks, electricity). Another aim is to understand how a high pathogen burden influences health and well‐being during development and adulthood. A third aim addresses how modernization shapes human life histories and sociality. Here we outline the project's goals, history, and main findings since its inception in 2002. We reflect on the implications of current findings and highlight the need for more coordinated ethnographic and biomedical study of contemporary nonindustrial populations to address broad questions that can situate evolutionary anthropology in a key position within the social and life sciences.